EXPLANATION
Given the sequence: -71, -85.2, -102.24, -122.688
The common ratio is given by the expression:
a_n = a_0* r^(n-1)
Check wheter the ratio is constant:
-71, -85.2, -102.24, -122.688
Compute the ratios of all the adjacent terms:
![r=(a_(n+1))/(a_n)](https://img.qammunity.org/2023/formulas/mathematics/college/dodjshk5o2e3uxfo5eit896fi3u6te1j8e.png)
![(-85.2)/(-71)=1.2,(-102.24)/(-85.2)=1.2](https://img.qammunity.org/2023/formulas/mathematics/college/isc94y12s47uaylgvcagpprujkuvnc8084.png)
The ratio of all the adjacent terms is the same and equl to
r=1.2
The first element of the sequence is:
a_1 = -71